Left ventricle accessory antero-septal papillary muscle: an echocardiography and cardiac MRI case-series report - Angheloiu George O.; Biederman Robert W. (Sciendo, 2022)
Background. We studied by means of echocardiography and cardiac MRI (CMR) the occurrence of an accessory papillary muscle that unites mostly the left ventricle (LV) apex with the basal antero-septum in the immediate vicinity of left ventricle outflow tract (LVOT) in patients with and without hypertrophic cardiomyopathy (HOCM).